GAYA HIDUP HEDONIS DALAM PERILAKU KONSUMTIF (STUDI KASUS MAHASISWA ANGKATAN 2021 PRODI ADMINISTRASI BISNIS FAKULTAS ILMU SOSIAL DAN ILMU POLITIK USU) : Gaya Hidup Hedonis dalam Perilaku Konsumtif pada Mahasiswa Prodi Administrasi Bisnis Fakultas Ilmu Sosial dan Ilmu Politik USU Angkatan 2021, Faktor-Faktor yang Mempengaruhi Mahasiswa Program Studi Administrasi Bisnis di Fakultas Ilmu Sosial dan Ilmu Politik USU Angkatan 2021 Menjalani Gaya Hidup Hedonis, Dampak Gaya Hidup Hedonis dalam Perilaku - Asri Lestari; Rivanka, Weny; Lestari, Dini (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2023)
This study aims to find out how big the hedonic lifestyle is in consumptive behavior in students of the Business Administration Study Program, Faculty of Social and Political Sciences,USU as well as the factors that influence and impact the hedonic lifestyle in consumptive behavior. This research is type of qualitative research. The population in this study were students of the Department of Business Administration, Faculty of Social and Political Sciences, USU Class of 2021. The sample in this study was 6 students majoring in Business Administration class 2021 class 4A. The sampling technique that can be used in this research is random sampling. Data analysis techniques used are data reduction, data presentation, and conclusions. The results of the study show that the hedonic lifestyle in consumptive behavior by students of the Business Administration Study Program, USU's Faculty of Social and Political Sciences, has various forms. Some students tend to choose a consumptive lifestyle in terms of fashion, while others are more inclined to social activities such as traveling and hanging out in popular places. Factors that influence students to live a hedonic lifestyle are personal preferences for modern life and family support. The positive impact of a hedonic lifestyle is increasing self-confidence and providing pleasant social experiences. The negative impacts are excessive consumption, priority imbalance, dissatisfaction, and uncontrolled financial spending.